Trypanosome co-infections increase in a declining marsupial population. Issue 2 (August 2018) - Godfrey, Stephanie S.; Keatley, Sarah; Botero, Adriana; Thompson, Craig K.; Wayne, Adrian F.; Lymbery, Alan J.; Morris, Keith; Thompson, R.C. Andrew
Abstract: Understanding the impacts of parasites on wildlife is growing in importance as diseases pose a threat to wildlife populations. Woylie (syn. brush-tailed bettong, Bettongia penicillata ) populations have undergone enigmatic declines in south-western Western Australia over the past decade. Trypanosomes have been suggested as a possible factor contributing towards these declines because of their high prevalence in the declining population. We asked whether temporal patterns of infection with Trypanosoma spp. were associated with the decline patterns of the host, or if other factors (host sex, body condition, co-infection or rainfall) were more influential in predicting infection patterns. Species-specific nested PCRs were used to detect the two most common trypanosomes ( T. copemani and T. vegrandis ) from 444 woylie blood samples collected between 2006 and 2012. Time relative to the decline (year) and an interaction with co-infection by the other trypanosome best explained patterns of infection for both trypanosomes. The prevalence of single species infections for both T. copemani and T. vegrandis was lower after the population crash, however, the occurrence of co-infections increased after the crash compared to before the crash. Our results suggest an interaction between the two parasites with the decline of their host, leading to a higher level of co-infection after the decline. We discuss the possible mechanisms that may have led to a higher level of co-infection after the population crash, and highlight the importance of considering co-infection when investigating the role of parasites in species declines. Graphical abstract: Image 1 Highlights: Woylie (bettong) populations have declined by >90% over 10 years. Prevalence of Trypanosoma copemani and T. vegrandis increased during the decline, and reset to a lower level after the crash. Overall prevalence of both Trypanosoma spp. decreased during the decline. The proportion of hosts co-infected with both species of Trypanosoma spp. increased after the population crash. Highlights the need to consider co-infection and the effects of declining host populations on parasite prevalence.